Predict-Observe-Explain Strategy: Effects on Students’ Achievement and Attitude towards Physics - Venida, Ariel Corral; Sigua, Eivan Mark Sunga (Jurnal Pendidikan MIPA, 2020)
This study employed a quasi-experimental research using the pretest-posttest design to determine the effect of Predict-Observe-Explain (POE) Strategy on students‟ achievement and attitude towards physics. A total of fifty-nine grade seven students from two intact heterogeneous classes participated in this study. The engage-explore-explain-elaborate-evaluate (5E‟s) learning cycle was utilized in teaching the control group while the POE strategy was utilized in teaching the experimental group. T-test was used in determining the significant differences between the two groups and within each group in terms of achievement and attitude. The findings of the study showed a significant difference (p = 0.00) in the achievement scores of the two groups in the posttest. It was further revealed that the experimental group (m = 11.47) performed better in the posttest than the control group (m = 8.86), and registered a significant change in attitude towards physics (p = 0.00) from neutral (m = 3.38) to positive (m = 3.76), while the control group maintained a neutral attitude. This suggests that the POE strategy positively influenced the academic performance and attitude of the students towards physics. Keywords: predict-observe-explain, 5E‟s learning cycle, attitude towards physics, students‟ achievement. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp78-94